COATING PERFORMANCES OF CRIMEAN JUNIPER (Juniperus excelsa M. BIEB.) WOOD - Öncel,Mustafa (2019)
ABSTRACT The purpose of this study is to determine the varnish layer hardness and varnish adhesion strength of the varnished Crimean juniper (Juniperus excelsa M. Bieb.) wood growing naturally in the Kastamonu region of Turkey. Test samples were varnished with UV-resistant polyurethane alkyd resin high gloss varnish (PAV) and water-based acrylic resin gloss varnish (WBAV). The varnish adhesion strength test was carried out by using universal testing machine. The varnish layer hardness was measured by using König pendulum hardness tester. Additionally, the colour properties were measured by spectrophotometer equipment that used the L*a*b* colour space. The adhesion strength of the polyurethane varnish and the water-based varnish were determined 2.81 MPa and 2.25 MPa respectively. Surface hardness value for water-based varnish and polyurethane varnish were determined 71 and 25 oscillation respectively. Detecting the performance of polyurethane and water-based varnish applications for the Crimean juniper wood will provide guidance in which type of varnish will be better for finishing. As a result, in varnish applications of the wood, it is recommended that water-based acrylic varnish should be applied when surface hardness is required. In addition, polyurethane alkyd varnish should be applied when better surface adhesion strength is desired.